Pengaruh Faktor Internal Dan Eksternal Terhadap Profitabilitas Pada Bank Syariah Indonesia - Nurjanah, Nurjanah; Wahyu Bima Susanto; Alfian (J-EBIS (Jurnal Ekonomi dan Bisnis Islam), 2024)
The Islamic banking industry in Indonesia has experienced rapid growth in recent years, in line with the increasing demand for Sharia-based financial services. However, the profitability of Sharia Foreign Exchange Banks still faces complex challenges, both from internal factors and external factors. A deep understanding of the influence of these factors is essential to improve the financial performance of Islamic banks. quantitative research, using quarterly financial data from 2016-2023 and multiple regression analysis. The results of this study show that Non-Performing Financing (NPF) and Financing to Deposit Ratio (FDR) have a significant influence on Bank Muamalat's Return on Assets (ROA). Good NPF management contributes to increased profitability, while the increase in FDR reflects the efficiency of fund distribution which also improves the bank's financial performance. In contrast, the inflation variable and BI Rate did not show a significant influence on ROA. This can be explained by the difference in the operational mechanism of Islamic banks that do not use the interest system so the impact of changes in interest rates and inflation on profitability is more limited.